Engineering Ru atomic structures toward enhanced kinetics of hydrogen generation. (18th May 2021) - Fu, Wenzhao; Wang, Qianhong; Chen, Wenyao; Qian, Gang; Zhang, Jing; Chen, De; Yuan, Weikang; Zhou, Xinggui; Duan, Xuezhi
Highlights: Engineering of Ru atomic structure by fine-tuning Cl and Co coordination. Acid-leaching of bimetallic catalyst for a 4.1-fold increase of H2 generation rate. Cl geometric effects of site blockage and steric hindrance as the main factors. Kinetics switch from a Cl coverage-limited to a reactant activation regime. Abstract: Herein, we demonstrate a strategy of engineering Ru atomic structures by fine-tuning Cl and Co coordination to synergize the quantity and quality of Ru active sites for boosting hydrogen generation from ammonia borane hydrolysis, via engineering the Cl-free/Cl-containing monometallic Ru catalysts and Co-leaching/Co-containing bimetallic Ru-Co catalysts. Under similar Ru particle sizes, the correlation between Ru binding energy and hydrogen generation activity affords a quantitative discrimination of Ru electronic and geometric contributions, where the site blockage and steric hindrance of Ru by Cl are more detrimental to hydrogen generation compared with the electronic modification by charge donation from Co to Ru. Reversely, the acid-leaching of Co from bimetallic catalysts creates abundant edge-like Ru active sites with much lower H2 O activation barrier, as indicated by the kinetics switch from a Cl coverage-limited regime to a reactant activation regime, thus yielding a significant 4.1-fold increase in hydrogen generation activity.